ICARE-BASED PHYSICS E-MODULE DEVELOPMENT TO ENHANCE PROBLEM SOLVING AND COMMUNICATION ON PRESSURE CONCEPTS - Alma; Darsikin; Haeruddin (Jurnal Ilmu Pendidikan Indonesia, 2025)
This study aims to develop an ICARE-based physics e-module (Introduction, Connecting, Application, Reflection, Extension) that is effective in enhancing students’ problem-solving and communication skills. The research utilized a Research and Development (R&D) approach, following the ADDIE development model. The population and sample consisted of all students from class VIII B at SMPN 4 Tanantovea. Data collection methods included the validation of the e-module by two expert validators, student questionnaires, essay tests administered twice before (pre-test) and after (post-test) the learning process to assess problem-solving skills, and observation sheets used across three sessions to evaluate students’ communication skills. The data were analyzed descriptively using statistical tools. The results indicated that the e-module was rated as highly feasible, with a validation score of 93%. Its effectiveness in improving students’ problem-solving skills was categorized as very high, with a Cohen’s d effect size of 7.126. In terms of communication skills, the average student score after using the ICARE-based physics e-module was 26.45 (47%) in the first session, 32.1 (57%) in the second session, and 44.6 (80%) in the third session. Based on these results, the ICARE-based physics e-module is considered highly suitable for use in classroom learning.